An analysis of fatal and non‐fatal injuries and injury severity factors among electric power industry workers. Issue 11 (27th June 2016) - Fordyce, Tiffani A.; Leonhard, Megan J.; Watson, Heather N.; Mezei, Gabor; Vergara, Ximena P.; Krishen, Lovely
Abstract: Background: The electric power industry represents a unique subset of the U.S. workforce. We aimed to evaluate the relationships between occupational category, nature of injury, and injury severity among electric power industry workers. Methods: The Occupational Health and Safety Database (1995–2013) was used to calculate injury rates, assess patterns of injury severity, and identify at‐risk occupations in this population. Results: Over the surveillance period, a total of 63, 193 injuries were reported. Overall, and severe injury rates were 3.20 and 0.52 per 100 employee‐years, respectively. The fatal injury rate was 3.29 per 100, 000 employee‐years. Line workers experienced the highest risk for fatal injuries and second highest for non‐fatal severe injuries, following meter readers. The most severe non‐fatal injuries were hernia and rupture; multiple injuries; and CTD/RSI. Fatal injuries were most commonly associated with vehicle collisions and contact with electric current. Conclusions: Industry specific surveillance and interventions tailored to high‐risk occupations are needed to further reduce severe injuries in this population. Am. J. Ind. Med. 59:948–958, 2016. © 2016 Wiley Periodicals, Inc.